Numerical analysis of shell and tube heat exchanger with convex-cut baffles (2014)
In this work, 3D numerical simulation for shell and tube heat exchanger is carried out with a commercial CFD code, COMSOL Multiphysics when utilizes the continuity, momentum and energy equations. It was discovered that much of the heat transfer was due to the cross flow at the tube bundles. The pressure drop increases rapidly while trying to increase the heat transfer rate by increasing the flow rate and this was in conformity with facts from literature. Performance of two shell and tube heat exchanger models were predicted, one with standard single-segmental baffles, STHE_SS (25% standard cut) and other with convex cut baffle, STHE_CS (30% convex cut). The STHE_SS has higher heat transfer rate and higher pressure drop than the STHE_CS for range of Reynolds number studied, a better performance ratio from Re ~ 4600 over STHE SS was recorded for STHE CS